Association Study of Coronary Artery Disease-Associated Genome-Wide Significant SNPs with Coronary Stenosis in Pakistani Population. (27th June 2020) - Cheema, Asma Naseer; Pirim, Dilek; Wang, Xingbin; Ali, Jabar; Bhatti, Attya; John, Peter; Feingold, Eleanor; Demirci, F. Yesim; Kamboh, M. Ilyas
Abstract : Genome-wide association studies (GWAS) of coronary artery disease (CAD) have revealed multiple genetic risk loci. We assessed the association of 47 genome-wide significant single-nucleotide polymorphisms (SNPs) at 43 CAD loci with coronary stenosis in a Pakistani sample comprising 663 clinically ascertained and angiographically confirmed cases. Genotypes were determined using the iPLEX Gold technology. All statistical analyses were performed using R software. Linkage disequilibrium (LD) between significant SNPs was determined using SNAP web portal, and functional annotation of SNPs was performed using the RegulomeDB and Genotype-Tissue Expression (GTEx) databases. Genotyping comparison was made between cases with severe stenosis (≥70%) and mild/minimal stenosis (<30%). Five SNPs demonstrated significant associations: three with additive genetic models PLG /rs4252120 (p = 0.0078 ), KIAA1462 /rs2505083 (p = 0.005 ), and SLC22A3 /rs2048327 (p = 0.045 ) and two with recessive models SORT1 /rs602633 (p = 0.005 ) and UBE2Z /rs46522 (p = 0.03 ). PLG /rs4252120 was in LD with two functional PLG variants (rs4252126 and rs4252135), each with a RegulomeDB score of 1f. Likewise, KIAA1462 /rs2505083 was in LD with a functional SNP, KIAA1462 /rs3739998, having a RegulomeDB score of 2b. In the GTEx database, KIAA1462 /rs2505083, SLC22A3 /rs2048327, SORT1 /rs602633, and UBE2Z /rs46522 SNPs were found to be expression quantitative trait loci (eQTLs) in CAD-associated tissues. In conclusion, five genome-wide significant SNPs previously reported in European GWAS were replicated in the Pakistani sample. Further association studies on larger non-European populations are needed to understand the worldwide genetic architecture of CAD.